Comparative analysis of PD-L1 expression and molecular alterations in primary versus metastatic lung adenocarcinoma: a real-world study in China - Chen, Gang; Yu, Yang; Qi, Youchao; Li, Guangxu; Li, Ning; Meng, Fande (Frontiers in Oncology, 2024)
ObjectivesProgrammed death-ligand 1 (PD-L1) is the only Food and Drug Administration-approved biomarker for monitoring response to immune checkpoint inhibitor (ICI) therapy in patients with lung adenocarcinoma. Understanding the nuances of molecular phenotypes, clinical attributes, and PD-L1 expression levels in primary and metastatic lung adenocarcinoma may help predict response to therapy and assist in the clinical management of lung adenocarcinoma.MethodsA total of 235 primary and metastatic lesion specimens from patients with non-small cell lung cancer (NSCLC) an institution in Shandong, China were analyzed. PD-L1 expression was assessed by immunohistochemistry using the 22C3 antibody, and the molecular phenotype was determined by next-generation sequencing of 450 genes. The molecular phenotypes of the primary and metastatic lesions were compared.ResultsElevated PD-L1 expression was significantly associated with advanced and metastatic disease (P = 0.001). The distribution of PD-L1 expression varied based on the anatomical location, showing a higher frequency of elevated PD-L1 expression in distal metastases than in the primary tumor. Metastatic lesions exhibited a higher proportion of carcinogenic pathway gene alterations and a greater number of DNA damage-repair pathway gene alterations than the primary lesions. Notably, CDKN2A copy number deletions were more prevalent in metastatic lesions than in primary lesions. Clinical data stemming from research conducted at the Memorial Sloan Kettering Cancer Center revealed an association between the absence of CDKN2A expression and a poorer prognosis in stage I lung adenocarcinoma.ConclusionSamples of metastatic tumors exhibited a higher proportion of elevated PD-L1 expression, a greater number of pathway alterations, and a higher occurrence of CDKN2A copy number deletions than primary samples. This highlights the importance of reinforcing the clinical management and follow-up of patients with CDKN2A deficiency, particularly within the subset of stage I lung adenocarcinoma.